ATTITUDE OF UNDERGRADUATE STUDENTS TO UNSOLICITED SMS ADVERTISING BY GSM OPERATORS - Olayinka, Awofadeju Peter; Ewuola Philip Olubunmi (IJRDO- Journal of Educational Research, 2019)
This research was carried out to examine the attitude of undergraduate students to unsolicited SMS advertising by GSM operators, using the undergraduate students of Achievers University, Owo, Ondo State as the case study. Survey method of gathering data was adopted for this paper by distributing well-developed questionnaire to elicit responses from the respondents, the sample size of which was 120. The findings clearly showed that GSM operators’ unsolicited SMS advertisements generates unfavourable attitudes and they are mostly unbeneficial, unexciting, confusing, misleading, and irritating. In addition, they are neither of any informational values nor relevant because the messages were not permitted by the subscribers that receive them, which is why they delete them immediately after receiving them. Therefore, sending such unsolicited messages should be discontinued.